Experimental and numerical investigation on dynamic response of a four-tier container stack and lashing system subject to rolling and pitching excitation - Li, Chuntong; Wang, Deyu; Liu, Jiaqi; Cai, Zhonghua (Applied ocean research, 2021)
This research aims to investigate the dynamic responses of the lashing force, twist lock force, and container stack displacement under conditions close to real, providing a better understanding of the mechanism behind container damage and loss. Based on Froude scaling laws, a four-tier 20-ft ISO freight container stack and lashing assembly scaled model was built. The rolling and pitching driving excitation is provided by a shaking table. Input variables for the experimental and numerical simulation include driving excitation (amplitude and frequency), lashing methods (internal and external), twist lock gap (horizontal and vertical), contact and friction between adjacent corner castings. Output variables of the system contain the lashing force, twist lock's tensile and shear force as well as displacement of the container stack. The results of the present study are compared via numerical simulation, experiments, and theoretical calculations, suggesting that the external lashing is superior to the internal lashing when encountering high stack and heavy stowage. There are mutual coupling effects between the lashing methods, lashing force, twist lock force and twist lock gap. Moreover, decreasing the gap can minimize the stack displacement and lashing force, while it is not a viable solution to reduce the twist lock force.